A Silent Voice : Words of Reassurance - Book 4 - Oima, Yoshitoki; LeCroy, Steven; Mizuno, Hiroko; (Letterer); Applegate, Ben; Hashimoto, Haruko (New York : Kodansha Comics, 2015)
"Shoya is a bully. When Shoko, a girl who cant hear, enters his elementary school class, she becomes their favorite target, and Shoya and his friends goad each other into devising new tortures for her. But the childrens cruelty goes too far. Shoko is forced to leave the school, and Shoya ends up shouldering all the blame. Six years later, the two meet again. Can Shoya make up for his past mistakes, or is it too late?"--provided from Amazon.com.
"T, ages 13+"--Back cover.
Translated from Japanese.
Keywords: Deaf children -- Comic books, strips, etc; Juvenile fiction; Bullying -- Comic books, strips, etc; Juvenile fiction; Bullies -- Comic books, strips, etc; Juvenile fiction; Conduct of life -- Comic books, strips, etc; Juvenile fiction; School children -- Comic books, strips, etc; Juvenile fiction; Teenagers -- Comic books, strips, etc; Juvenile fiction; Comic books, strips, etc. -- Japan; Translations into English; Graphic novels -- Juvenile fiction; Manga; Comics (Graphic works); Graphic novels; Translations